Moderate Islamic Da'wah in the New Normal Era (KH. Afifuddin Muhajir And KH. Abdul Moqsith Ghazali Online Reading Study) - Ahmad Dalhar Muarif; Jamal Ma'mur Asmani (The Institute of Research and Service Community IPMAFA Pati, 2021)
Islamic da'wah through online media is able to provide another form of delivering da'wah in the new normal era. The development of public opinion must be balanced with news that is peaceful, therefore it is necessary to preach about moderate Islam. Among the figures who preach via social media are KH. Afifuddin Muhajir and KH. Abdul Moqsith Ghazali. Moderate Islam has a character based on divinity, based on the instructions of the prophet, compatible with human nature, free from conflict, steady and consistent, universal and comprehensive, wise, balanced and free from excessive actions. The method used in this study is a qualitative method. This study uses a phenomenological approach. Analysis using discourse content analysis. This research takes data from You Tube content. Afifuddin Muhajir and KH. Abdul Moqsith Ghazali. Moderate Islamic da'wah carried by KH. Afifuddin Muhajir and KH. Abdul Moqsith Ghazali provides a high portion of reasoning and is oriented towards human respect. Both of them are experts in ushul fiqh and study Sufism, so that these two disciplines greatly influence their thinking so that they have a rationalist-humanist pattern. rationalist-humanist is da'wah in the way of thinking al-adalah, at-tawazun, at-tawasuth and at-tasamuh which makes human beings an object that should be respected and valued as a creature of God's creation.